RESEARCH ABOUT TEACHING STYLES. CONTRIBUTIONS TO IMPROVE TEACHING SCIENCE - Ventura, Ana Clara (2013)
The aim of this paper is to clarify conceptual and operational aspects of the construct “teachingstyles” with its three distinctive properties: relative stability, multidimensionality and valueneutrality. Moreover, it analyzes the points of view that are shared for many empirical studies:teachers transmit knowledge and typical forms of learning; teaching styles differ according tothe type of subject taught, the match between the teaching styles and learning styles improveknowledge acquisition. In summary, this paper provides knowledge and strategies that contributeto training in science teaching and, therefore, to strengthen effective teaching practices.